Improving the stimulation selectivity in the human cochlea by strategic selection of the current return electrode - Cakmak, Ozan; Pal, Saikat; Sahin, Mesut (Frontiers in Audiology and Otology, 2023)
The hearing quality provided by cochlear implants is poorly predicted by computer simulations. A high-resolution, human-specific cochlear anatomy is crucial for the accuracy of predictions. In this study, the standard multipolar stimulation paradigms are revisited and Rattay's Activating Function is evaluated in a finite element model of a realistic cochlear geometry that is based on μ-CT images and a commercial lead. The stimulation thresholds across the cochlear fibers were investigated for monopolar, bipolar, tripolar, and a novel (distant) bipolar electrode configuration using an active compartmental nerve model based on Schwartz-Eikhof-Frijns membrane dynamics. The results suggest that jumping of the stimulation point from the vicinity of the cathodic electrode to distant fibers, especially to the low frequency (apical) region of the basilar membrane that is most critical to hearing, occurs more often with monopolar stimulation than other electrode configurations. Bipolar and tripolar electrodes near the apical region did not provide a large threshold margin either. On the other hand, the threshold margin could be improved by proper selection of the electrode for the return current with bipolar stimulation, a technique named here as distant bipolar. The results also demonstrate the significance of having a realistic cochlear geometry in computer models for accurate interpretation for multipolar stimulation paradigms. More selective and focal stimulation may be possible by designing the electrode carrier shape and positioning of the current return electrodes more strategically. This is needed particularly in the apical turn of the cochlea where the current stimulation methods are the least selective.